(3fRgI GdeMH hGdCMHGHs
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd ddYGTbjf HCMcGe GdZQGe QVkG hHYO (B: (3aEfi LeYJ gPG GdcJGH , hLYdJg fRgI ddeMH hGdCMHGH hLeYJ ajg ef GdCTYGQ hGdfhGOQ hGdMcGjGJ hGdCNHGQ s
(3BNQgG (B:s
(3SCdJc Gddg Ef YGjfJ di NWC aGSJQ aEf NjQ GdfGS ef SJQG Je GdeLehY GdeHGQc s
(3YdjgG eWGdYI hJedc SfI (B1004(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(539) s
Keywords: (3GdCOHs